Design for Learning Principles, Processes, and Praxis - McDonald, Jason K.; West, Richard E. (Open textbook library., 2021)
Our purpose in this book is twofold. First, we introduce the basic skill set and knowledge base used by practicing instructional designers. We do this through chapters contributed by experts in the field who have either academic, research-based backgrounds, or practical, on-the-job experience (or both). Our goal is that students in introductory instructional design courses will be able to use this book as a guide for completing a basic instructional design project. We also hope the book is useful as a ready resource for more advanced students or others seeking to develop their instructional design knowledge and skills.